Effects in Latin America of the Russia-Ukraine conflict from the point of view of public international law - Mendoza Escalante, Pablo Ricardo (2023)
This article analyzed the armed conflict between Russia and Ukraine regarding its political and economic effects in Latin America from the point of view of public international law, depending on the impact of international aspects such as the global geopolitical rearrangement, international relations in the different markets, the generation of new regional alliances. Based on this, the objectives were set to identify the characteristics of armed conflicts from the perspective of international law, to characterize the Russia-Ukraine conflict from a geopolitical perspective and finally, to analyze the effects of this conflict in some Latin American countries since February 2022. Documentary research with a qualitative descriptive and analytical approach was used. As findings, we found the reappearance of traces of the cold war, but with current nuances with new alliances such as the global south and the use of technologies that decisively influence the new paradigm of armed conflicts. It was concluded that, in Latin America, the economic and political effects are concentrated in the dynamics of the international payment system; the price of energy and oil; as well as in the food sovereignty of the States.